Water Pollution and Water Quality Assessment of Major Transboundary Rivers from Banat (Romania) - Andreea-Mihaela Dunca (Journal of Chemistry)
This study focuses on water resources management and shows the need to enforce the existing international bilateral agreements and to implement the Water Framework Directive of the European Union in order to improve the water quantity and quality received by a downstream country of a common watershed, like Timiş-Bega hydrographical basin, shared by two countries (Romania and Serbia). The spatial trend of water quality index (WQI) and its subindexes are important for determining the locations of major pollutant sources that contribute to water quality depletion in this basin. We compared the values of WQI obtained for 10 sections of the two most important rivers from Banat, which have a great importance for socioeconomic life in southwestern part of Romania and in northeastern part of Serbia. In order to assess the water quality, we calculated the WQI for a long period of time (2004–2014), taking into account the maximum, minimum, and the mean annual values of physical, chemical, and biological parameters (DO, pH, BOD5, temperature, total P, N-NO2−, and turbidity). This article highlights the importance of using the water quality index which has not been sufficiently explored in Romania and for transboundary rivers and which is very useful in improving rivers water quality.